On fork-tailed crab spiders: Two new species of Sidymella Strand, 1942 (Araneae: Thomisidae) from Ecuador - Díaz-Guevara, David R.; Machado, Miguel (Zootaxa, 2026)
Two new species from the family Thomisidae are described from Ecuador: Sidymella ayahuma sp. nov. from the Andean chocó region in Northwestern Ecuador (♀) and Sidymella malefica sp. nov. (♀) from the Andes region in central Ecuador.